RANCANG BANGUN APLIKASI MOBILE BECAK ONLINE - Richasanty Septima S; Ira Zulfa (Elkom : Jurnal Elektronika dan Komputer, 2021)
Online rickshaw application is an application that serves to help the performance of the community in traveling. Pedicabs are widely used by residents, especially in Takengon, pedicabs are one of the means of land transportation that is in great demand by the community, especially the middle to lower classes. However, pedicabs can not be found all the time, sometimes we have to wait a long time, have to walk to get a pedicab, even pedicabs are only at a crossroads. Lack of information between rickshaw drivers and passengers and limited public transport lanes. With this online transportation application, answering the problems of the people, especially in the Takengon area. How to use it so easily that the target community must have special skil…